Інтертекстуальні елементи в історичному романі Генрика Сенкевича «Вогнем і мечем» - Ляшов, Назар; Lyashov, Nazar (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано параметри інтертекстуальності щодо використан- ня латинських слів, висловів, цитат з античних творів в історичному романі Г. Сенкевича. Досліджено наявність інтертексту на формальному рівні, що на- дає творові специфічного звучання. Виділено певний масив понятійного змісту латини, яка є засобом особливого історичного світу твору.The article focuses on the parameters of intertextuality including the use of Latin words and phrases and quotations from ancient literature in Henryk Sienkiewicz’s historical novel “With Fire and Sword”. On the formal level the intertextual elements determine specific tonality of the novel. Conceptual content of the Latin phraseology constitutes the historical world of the novel. The author’s tendency of using Latin words and phrases proves to comprise three forms: single words and word combinations; famous sayings and proverbs; and quotations from ancient literature. The intertextual references to Latin origins and other historical background define the symbolic order of the novel.
Intertextual Elements in Henryk Sienkiewicz’s Historical Novel “With Fire and Sword”
Keywords: інтертекстуальність; античність; латинські слова та словосполучення; історичний роман; Intertextuality; antiquity; Latin words and phrases; historical novel